Analisis Capital Budgeting Dalam Rencana Investasi Aktiva Tetap di Perusahaan Pelayaran (Studi Kasus Pembelian Kapal Peti Kemas di PT. SI) - Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2019)
The purpose of this study is to apply a capital budgeting analysis in the investment plan of fixed assets in shipping companies, from this study it can be seen whether the addition of fixed assets can be said to be feasible or not to be carried out. In terms of financial aspects, the data used are data on investment needs, production plans, depreciation, results of operations, profits and cash flow. The capital budgeting method or investment feasibility assessment used is the Payback Period, Net Present Value, Internal Rate of Return, and Benefit Cost Ratio. The results of research investment in the purchase of container ships PT. SI is eligible according to the calculation of Payback Period, Net Present Value (NPV), and Internal Rate of Return (IRR). The Payback Period is 3.5 months faster than the economic life of container ships, which is 20 years. NPV has a positive value, which is 170,007,712, and IRR has a value of 13.47% or 0.47% above bank interest, which is 13%. However, from the calculation of the Benefit - Cost Ratio produces a value of 0.161. Therefore, investment in the purchase of container ships PT. SI will be rejected.